A Simulation Trainer's Educational Competence in the Process of Forming Students' Professional Competence - Mahmudovna, Imamova Shafoat (International Journal on Integrated Education, 2023)
Students in higher education's applied mathematics program are instructed on the topic of "computer mathematical systems." The area of science has a variety of instructional guides, textbooks, and electronic textbooks. In this essay, we evaluate the pedagogical potential of the simulator in the process of developing students' professional competence in the teaching of "Computer Mathematical Systems."